Divergent paths in digital sovereignty: a comparative analysis of EU and US regulatory and strategic frameworks - Bukonkin, Dzianis A. (Journal of the Belarusian State University. International Relations, 2025)
This study compares how the EU and the US pursue digital sovereignty as a component of national digital security policy. The analysis examines the normative and legal frameworks of each actor, as well as their engagement on international platforms. It also explores the EU’s multilateralist orientation alongside the US’ alliance-building and leadership-focused paradigm. Through case studies, it identifies the challenges and risks each faces in implementing information sovereignty strategies and evaluates the diplomatic and legal ramifications of their respective approaches. The analysis also tracks shifts in US perspectives on collaboration with traditional partners. The conclusion assesses prospects for reconciling US and EU approaches within transatlantic relations.
Keywords: digital sovereignty; legal frameworks; global governance; data policy; geopolitical strategy